Surface Hydrocarbons from the Leaves of Trianthema portuiacastrum Linn. - LASKAR, SUBRATA; BANERJEE, GAUTAM; MUKHERJEE, AMBARISH (Asian Journal of Chemistry, 2010)
Hydrocarbons from the surface wax of the fresh leaves of Trianthema portulacastrum Linn. have been isolated and characterized and their relative distribution determined through GLC studies. The considerable occurrence of branched chain hydrocarbons may be an indication of the characteristics of lower plants based on taxonomy.